2002
DOI: 10.2190/5hcy-u2q9-kvgl-8m3k
|View full text |Cite
|
Sign up to set email alerts
|

It's a Long Way Home: International Student Adjustment to Living in the United States

Abstract: This study addresses the need for information helpful in retaining international college students studying in the United States. This research compares the adjustment of 182 international students to a comparison sample of American students to determine whether students coming to the United States from abroad have greater difficulty adjusting to college life. International students are more likely to feel lonely, homesick, and as if they had left part of themselves at home. In addition, this study confirms the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 16 publications
(10 reference statements)
5
78
3
1
Order By: Relevance
“…Zhang and Brunton (2007) found that 55% of their sample of Chinese international students in New Zealand were unhappy with their opportunities to make friendships with locals, and 71% reported that they would like to have more local friends. In other studies, international students have reported perceptions of less social support than domestic students (Hechanova-Alampay, Beehr, Christiansen, & Van Horn, 2002;Khawaja & Dempsey, 2008), and more loneliness and homesickness (Parr & Bradley, 1991;Rajapaksa & Dundes, 2002). Contrary to these findings, Klomegah (2006) found no significant difference in levels of feeling alienated between domestic and international students in the U.S.A.…”
Section: Sociocultural Stressorsmentioning
confidence: 90%
“…Zhang and Brunton (2007) found that 55% of their sample of Chinese international students in New Zealand were unhappy with their opportunities to make friendships with locals, and 71% reported that they would like to have more local friends. In other studies, international students have reported perceptions of less social support than domestic students (Hechanova-Alampay, Beehr, Christiansen, & Van Horn, 2002;Khawaja & Dempsey, 2008), and more loneliness and homesickness (Parr & Bradley, 1991;Rajapaksa & Dundes, 2002). Contrary to these findings, Klomegah (2006) found no significant difference in levels of feeling alienated between domestic and international students in the U.S.A.…”
Section: Sociocultural Stressorsmentioning
confidence: 90%
“…[24] They experience homesickness, are often lonely, miss family and friends, and require emotional support from family units to achieve success on a programme. [10,25] Nurses and managers in our study reinforced closeness to culture, social networks and family as reasons for application.…”
Section: Discussionmentioning
confidence: 61%
“…Studies in international education showed that while academic integration challenges were present, social adjustment challenges prevailed (evidenced by, for example, international students' frequent feelings of stress, anxiety, depression, loneliness, homesickness, as well as experiences of discrimination; also, in general, international students reported a lack of friendships with domestic students) (Andrade, 2006;CBIE, 2013;Rajapaksa & Dundes, 2002). In addition, although institutions of higher education have developed professional services to support international student integration (international student centres have typically offered a combination of services, such as student orientation, buddy system or peer program; professional advice on issues related to immigration, student work permit or taxation; professional counseling), Popadiuk and Arthur (2004) suggested that international students remain reluctant to use any type of professional counseling and actually prefer to either -suffer alone‖ or seek the support of family and close friends.…”
Section: Resultsmentioning
confidence: 99%
“…with other international students); and experiences of discrimination (CBIE, 2013;Popadiuk & Arthur, 2004;Rajapaksa & Dundes, 2002). In a further review of various studies of international students' social adjustment, Andrade (2006) concluded that variables such as country of origin (and the extent of cultural dissimilarity), gender and number of years in school affected the degree of social adjustment of international students.…”
Section: Introductionmentioning
confidence: 99%